Hitler's prisons : legal terror in Nazi Germany - Wachsmann, Nikolaus 1971- (Yale University Press, 2004)
The Weimar prison, 1918-1933 -- Inside the prison -- The crusade against "community aliens" -- The Nazi web of terror -- Law in wartime -- Prison conditions -- Privilege and punishment -- Killing prisoners -- Final defeat -- The Nazi prison in perspective